FORGOT CALCIUM? ADMISSION IONIZED-CALCIUM IN TWO CIVILIAN RANDOMIZED CONTROLLED TRIALS OF PRE-HOSPITAL PLASMA FOR TRAUMATIC HEMORRHAGIC SHOCK - Moore, Hunter B. (J Trauma Acute Care Surg, 2020)
BACKGROUND: Randomized clinical trials(RCTs) support the use of pre-hospital plasma in traumatic hemorrhagic shock, especially in long transports. The citrate added to plasma binds with calcium, yet most pre-hospital trauma protocols have no guidelines for calcium replacement. We reviewed the experience of two recent pre-hospital plasma RCTs regarding admission ionized-calcium (i-Ca) blood levels and its impact on survival. We hypothesized that pre-hospital plasma is associated with hypocalcemia, which in turn is associated with lower survival. METHODS: We studied patients enrolled in two institutions participating in pre-hospital plasma RCTs (Control=Standard-of-care; Experimental=Plasma), with i-Ca collected prior to calcium supplementation. Adults with traumatic hemorrhagic shock(SBP≤70 mmHg or 71–90mmHg+HR≥108bpm) were eligible. We use generalized linear mixed models with random intercepts and Cox proportional hazards models with robust standard errors to account for clustered data by institution. Hypocalcemia was defined as i-Ca≤1.0mmol/L. RESULTS: Of 160 subjects(76% men), 48% received pre-hospital plasma, median age 40years(IQR:28–53), 71% suffered blunt trauma, median ISS=22(IQR:17–34). Pre-hospital plasma and control patients were similar regarding age, sex, ISS, blunt mechanism, and brain injury. Pre-hospital plasma recipients had significantly higher rates of hypocalcemia compared to controls (53% vs 36%, Adjusted Relative Risk, aRR=1.48; 95%CI: 1.03–2.12, p=0.03). Severe hypocalcemia was significantly associated with decreased survival(Adjusted Hazard Ratio:1.07;95%CI:1.02–1.13,p=0.01) and massive transfusion(aRR= 2.70;95%CI:1.13–6.46, p=0.03), after adjustment for confounders(randomization group, age, ISS, and shock index). CONCLUSION: Pre-hospital plasma in civilian trauma is associated with hypocalcemia, which in turn predicts lower survival and massive transfusion. These data underscore the need for explicit calcium supplementation guidelines in pre-hospital hemotherapy.